Novel use of telescoping growth rods in treatment of early onset scoliosis: An in vivo and in vitro study in a porcine model. Issue 4 (8th October 2018) - Vaudreuil, Nicholas; Xue, Jingbo; Ramanathan, Rahul; Tisherman, Robert; Dombrowski, Malcolm; Wang, Wen‐Jun; Bell, Kevin
Abstract : Introduction: Treatment of early‐onset scoliosis (EOS) can be difficult. Various forms of growing rods exist to correct deformity while delaying definitive spinal fusion. The disadvantage of traditional growing rods is need for repeated surgical lengthening procedures. Telescoping growth rods (TelGR) are a prototype new, guided growth technology with a rod mechanism that allows spontaneous longitudinal growth over time without manual lengthening. We hypothesized that the TelGR system will permit unrestricted growth with limited complications through 12 weeks in vivo, and that the range of motion (RoM) in each of three directions and stiffness of the TelGR system would not be significantly different than the rigid rod system in vitro . Materials and Methods: In vivo : Six immature pigs were surgically implanted with TelGR with cephalad fixation at T6‐7 and caudal fixation at T14‐L1. Radiographs of the involved vertebral segments were measured postoperatively and after 12 weeks. In vitro : A robotic testing system was utilized for flexibility tests in flexion‐extension (FE), lateral bending (LB), and axial rotation (AR) of eight immature porcine specimens (T3‐T15). Testing was performed on both dual rigid rods and bilateral TelGR with instrumentation at T4‐5 and T13‐14. Results: In vivo : Over the 12‐week period, the rod length of the TelGR increased an average of 65 mm. In vitro : TelGR demonstrated significantly increased motion in LB and AR RoM compared with rigid rods. No difference was noted in FE RoM. Discussion: The in vivo results in this study showed expected skeletal growth with spines instrumented with TelGR. In vitro findings of increased RoM in AR and LB suggest that the TelGR system may be less rigid than traditional growing rods. Treatment with TelGR might, if proven efficacious in the clinical setting, decrease the need for repeated surgical intervention compared with traditional growing rods. This study adds to the limited body of biomechanical evidence examining guided growth technology. Abstract : Telescoping growth rods (TelGR) are a prototype new, guided growth technology with a rod mechanism that allows spontaneous longitudinal growth over time without manual lengthening. The purpose of this laboratory pilot study was to evaluate the biomechanical characteristics with growth and stimulated mechanical loading of the TelGR system, using a porcine thoracic spine model. The in vivo and in vitro results suggest that the TGR system was successful in achieving noninvasive rod lengthening with growth over time and resulted in less rigidity than solid rods used in traditional growing rod procedures.